Optimal design for sustainable bioethanol supply chain considering detailed plant performance model - Corsano, Gabriela (2011)
The always increasing energy demand combined with the declining availability of fossil fuels is driving forces for the investigation of renewable energy sources. In this context, bioethanol is considered as one of the most appropriate solutions for short term gasoline substitution. Then, the motivation of this work is to propose a MINLP optimization model for a sustainable design and behavior analysis of sugar/ethanol supply chain (SC). A detailed model for ethanol plant design is embedded in the SC model, and therefore plant and SC designs are simultaneously obtained. Yeast production and residue recycles are taken into account in order to assess the environmental impact. The inclusion of sustainability issues in the model produces both economic and operative changes in SC and plant designs. The simultaneous optimization of these elements allows the evaluation of several compromises among design and process variables. These issues are highlighted throughout the evaluated studied cases.